THE EFFECT OF COMPUTER ASSISTANT INSTRUCTION ( CAI ) ON ADVANCED READING - Aprillia Widya Lestari; Fenny Thresia (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2021)
The study was conducted to find out the significant influence of Computer Assisted Instruction (CAI) on advanced reading at fourth semester of English Department Muhammadiyah University of Metro. Computer Assisted Instruction (CAI) is a technique to give instruction by using computer to the students and instructional approach where a computer is used to evaluate the learning outcomes. This research is an experimental research and the subject of the research are 40 students at fourth semester of English department. There are two 20 students for control group and 20 students for experimental group. The result of average score of pre-test at experimental group and control group are 1.36 and 1.39. It shows that the control group is higher than the experimental group. However, the result of the post test of the experimental group is higher the control group, they are 1.71 for the experimental group and 1.41 for the control group. It can be conclude that, there is significant influence in students’ reading comprehension after being taught by using Computer Assisted Instruction (CAI )